Revision of the genus Deltaspis Audinet-Serville, 1834 with systematic analysis and new taxa of Trachyderini with emarginate-truncate mandibles (Insecta: Coleoptera: Cerambycidae) - Eya, Bryan K. (Zootaxa, 2019)
The genera Deltaspis Audinet-Serville, 1834 and Muscidora, Thomson, 1864 (Coleoptera: Cerambycidae: Cerambycinae: Trachyderini) are revised. Two new genera Neoxoplus gen. nov. and Deltaspiopsis gen. nov., are described. Two species previously included in Deltaspis [D. cruentus, (LeConte, 1862), and D. ivae Beierl & Barchet-Beierl, 1999] are transferred to the new genus Neoxoplus with N. cruentus designated as the type species. Four other Deltaspis species [D. alutacea Bates, 1885, D. marginella Bates, 1891, D. nigripennis Bates, 1880, and D. tumacacorii (Knull, 1944)] are transferred to Muscidora Thomson, 1864. Two species [D. disparilis Bates, 1891, and D. variabilis Bates, 1891] are transferred to the new genus Deltaspiopsis with D. disparilis designated as type species, and the remaining species [D. moesta Bates, 1885, D. rubens Bates, 1885, and D. subopaca Chemsak & Linsley, 1982] are transferred to Crossidius LeConte, 1851. Keys to closely related genera, above mentioned genera and species along with illustrations of the available species in color are included. New species described include: Muscidora bezarki sp. nov. from south-central Mexico (Puebla, Oaxaca); Muscidora coriacea sp. nov. from southeastern Mexico (Oaxaca and Chiapas); Muscidora nigrescens clinei subsp. nov. (Jalisco); and Muscidora similis sp. nov. from western Mexico (Sinaloa and Sonora).